(untitled) (Polifonia, 2015)
Neste artigo, serão feitas as edições fac-similar e semidiplomática e comentários paleográficos de um manuscrito do século XVIII, testemunho pertencente ao Arquivo Público de Mato Grosso. Trata-se de uma carta datada de 12 de agosto de 1791 que versa sobre ordem expedida do presídio de Coimbra, da lavra do Sargento Mor Joaquim José Ferreira, enviada ao General das Capitanias de Mato Grosso e Cuiabá. Pretende-se contribuir com os estudos que se vêm empreendendo sobre a variedade de língua portuguesa trazida para a fronteira oeste do Brasil colônia pelos bandeirantes paulistas, a partir do século XVIII, através das monções. O estudo integra o projeto: “Para a História do Português Brasileiro-Mato Grosso”. PALAVRAS-CHAVE: manuscrito, edições, Capitania de Mato Grosso PALEOGRAPHIC CHARACTERISTICS IN LETTER FROM THE EIGHTEENTH CENTURY ABSTRACT: In this paper, fac-similar and semidiplomatic editions as weel as paleographic notes will be made based on an eighteenth-century manuscript belonging to the Public Archive of Mato Grosso. It is a letter dated on August 12th, 1791, which refers to an order issued from the Coimbra prison, written by the Major Sergeant Joaquim José Pereira, and sent to the General of the Captaincy of Mato Grosso and Cuiabá. This work is a contribution to the studies that have been undertaken on the Portuguese language variety brought to the western border of Colonial Brazil by pioneers from São Paulo in the eighteenth century. This paper is part of the project: "For the History of Brazilian Portuguese - Mato Grosso”. KEYWORDS: manuscript, editions, Captaincy of Mato Grosso